Conflict of Jurisdiction Between the Federal Supreme Court and The Court of Administrative Justice in Challenging Administrative Decisions in Iraq - Ameer Hussein Alawi Al-Ukayshi (International Journal of Law And Criminology, 2025)
A conflict occurs between two or more courts, such as the conflict that occurs between the ordinary judiciary and the administrative judiciary in countries that adopt a dual judicial system. All or some of the courts refuse to consider the case, claiming that it is not within their jurisdiction, so they refer it to another court, or each court maintains its jurisdiction to consider the case. In this case, the competent authority must be determined from among the judicial authorities or bodies with judicial jurisdiction. The Iraqi legislator adopted this principle by Law No. (106) of 1989, the second amendment to the Council of State Law No. (65) of 1979, and the federal system adopted it by virtue of the Law of Administration of the State for the Transitional Period in 2004 and the Permanent Constitution of 2005, due to the possibility of a conflict of jurisdiction occurring between the ordinary judiciary and the administrative judiciary. This article aims to define this conflict and its application in the event that a conflict of jurisdiction occurs between the Federal Supreme Court and the Administrative Judiciary Court in appealing administrative decisions in Iraq.